Chapter 幻の春の声. 近現代日本文学における「亀鳴く」/ The illusory voice of the spring: the motif of 'crying turtle' in modern and contemporary Japanese literarure - Cucinelli, Diego (Studi e saggi, 2020)
The turtle (kame) is of great importance in East Asian culture and it is seen as a supernatural creature. In Japanese literature, we can find examples of the turtle in works dating back to the Nara period, such as Tangokuni fudoki and Nihonshoki. Just like the crane, the turtle is a symbol of longevity. However, from the Kamakura period a new and unique interpretation of the turtle as the "singing/crying turtle" makes its appearance. Of this topos, known as kame naku, we can find only very few examples in literature until the Meiji era and the most known are the waka anthologies Shinsen waka rokujō and Fuboku wakashō, and Kyokutei Bakin's kigo collection Haikai saijiki shiorigusa. However, from the beginning of the modern age, kame naku has been used by many poets as a kigo connected to spring and its frequency has hugely increased. After the war, it began to appear not only in poetry but also in novels and essays. The best known examples of this being Mishima Yukio's short novel Chūsei, Uchida Hyakken's essay Kame naku ya, Kawakami Hiromi's work Oboreru. Using kame naku as a keyword, in this paper we will analyze the attitudes and approaches of modern and contemporary poets and novelists toward the topos.